A comprehensive performance comparison for segregated algorithms of flow and heat transfer in complicated geometries. (15th July 2008) - Wu, Z.G.; Qu, Z.G.; He, Ya-Ling; Tao, W.Q.
In this paper, a comprehensive performance comparison among CLEAR, SIMPLER and SIMPLEC algorithms at staggered grid system is performed for four incompressible fluid flow and heat transfer problems in complicated geometries. It is found that for most of the relaxation factor variation range CLEAR can appreciably enhance the convergence rate though it is slightly less robust than the other two algorithms. For the four problems tested, the ratio of iteration numbers of CLEAR over that of SIMPLER and SIMPLEC can reach as low as 0.18, 0.09 and the ratio of the CPU time as low as 0.23, 0.18, respectively.